Motor imagery ability in stroke patients: the relationship between implicit and explicit motor imagery measures - De Vries, Sjoerd; Tepper, Marga; Feenstra, Wya; Oosterveld, Hanneke; Boonstra, Anne M.; Otten, Bert (Frontiers in Human Neuroscience, 2013)
There is little consensus on how motor imagery ability should be measured in stroke patients. In particular it is unclear how two methods tapping different aspects of the motor imagery process relate to each other. The aim of this study was to investigate the relationship between implicit and explicit motor imagery ability by comparing performance of stroke patients and controls on a motor imagery questionnaire and a hand laterality judgment task (HLJT). Sixteen ischemic stroke patients (36±13 weeks post-stroke) and 16 controls, matched by age (51±10 years), gender (7 females) and handedness (3 left-handed), performed a HLJT and completed a motor imagery questionnaire. Our study shows that neither in the healthy controls nor in patients, a correlation is found between the HLJT and the motor imagery questionnaire. Although the patient group scored significantly lower than the control group on the visual motor imagery component (U= 60; p = 0.010) and the kinesthetic motor imagery component (U = 63.5; p = 0.015) of the questionnaire, there were no significant differences between patients and controls on accuracy scores of the HLJT. Analyses of the reaction time profiles of patients and controls showed that patient were still able to use an implicit motor imagery strategy in the HLJT task. Our results show that after stroke performance on tests that measure two different aspects of motor imagery ability, e.g. implicit and explicit motor imagery, can be differently affected. These results articulate the complex relation phenomenological experience and the different components of motor imagery have and caution the use of one tool as an instrument for use in screening, selecting and monitoring stroke patients in rehabilitation settings.